Modelling of precast concrete composite slab using finite and interface elements - Jaafar, Mohd Saleh; Wong, J. N.; Noorzaei, Jamaloddin; Thanoon, Waleed Abdulmalik (Universiti Putra Malaysia Press, 2009)
This study presents an efficient finite element analysis technique which shows great versatility in modelling of precast composite flooring system subjected to static loadings. The method incorporates sliding and opening in the analysis of composite structures using the interface element which was specifically designed to simulate the actual behaviour at the interfaces between contacting materials. A three-dimensional finite element model of the precast composite slab which exhibits discontinuous behaviour was performed to demonstrate the potential and applicability of the proposed method of analysis. The results of the analysis demonstrate that the overall response of a discontinuous system to external loading is significantly affected by the bonding condition at the interfaces between the contacting materials.